Temperatura superficial puente vehicular en la avenida Jorge Gaitán Cortés con avenida Quiroga (2022)
Civil constructions have been necessary since the beginning of time, thus allowing the social and economic progress of each population around the world, complying with Colombian technical standards, guaranteeing a correct performance in its design and execution. For this work we intend to analyze the effect of load thermal in the bridge under study, proposing design and maintenance parameters, because there are factors that influence the fatigue of the elements that make up the structure.